Siglec-9 Restrains Antibody-Dependent Natural Killer Cell Cytotoxicity against SARS-CoV-2 - Saini, Pratima; Adeniji, Opeyemi S.; Bordoloi, Devivasha; Kinslow, Jennifer; Martinson, Jeff; Parent, Danielle M.; Hong, Kai Ying; Koshy, Jane; Kulkarni, Abhijeet J.; Zilberstein, Netanel F.; Balk, Robert A.; Moy, James N.; et al. (mBio, 2023)
One mechanism that cancer cells use to evade natural killer cell immune surveillance is by expressing high levels of sialoglycans, which bind to Siglec-9, a glyco-immune checkpoint molecule on NK cells. This binding inhibits NK cell cytotoxicity. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection alters the immunological profiles of natural killer (NK) cells. However, whether NK antiviral functions are impaired during severe coronavirus disease 2019 (COVID-19) and what host factors modulate these functions remain unclear. We found that NK cells from hospitalized COVID-19 patients degranulate less against SARS-CoV-2 antigen-expressing cells (in direct cytolytic and antibody-dependent cell cytotoxicity [ADCC] assays) than NK cells from mild COVID-19 patients or negative controls. The lower NK degranulation was associated with higher plasma levels of SARS-CoV-2 nucleocapsid antigen. Phenotypic and functional analyses showed that NK cells expressing the glyco-immune checkpoint Siglec-9 elicited higher ADCC than Siglec-9 – NK cells. Consistently, Siglec-9 + NK cells exhibit an activated and mature phenotype with higher expression of CD16 (FcγRIII; mediator of ADCC), CD57 (maturation marker), and NKG2C (activating receptor), along with lower expression of the inhibitory receptor NKG2A, than Siglec-9 – CD56 dim NK cells. These data are consistent with the concept that the NK cell subpopulation expressing Siglec-9 is highly activated and cytotoxic. However, the Siglec-9 molecule itself is an inhibitory receptor that restrains NK cytotoxicity during cancer and other viral infections. Indeed, blocking Siglec-9 significantly enhanced the ADCC-mediated NK degranulation and lysis of SARS-CoV-2-antigen-positive target cells. These data support a model in which the Siglec-9 + CD56 dim NK subpopulation is cytotoxic even while it is restrained by the inhibitory effects of Siglec-9. Alleviating the Siglec-9-mediated restriction on NK cytotoxicity may further improve NK immune surveillance and presents an opportunity to develop novel immunotherapeutic tools against SARS-CoV-2 infected cells. IMPORTANCE One mechanism that cancer cells use to evade natural killer cell immune surveillance is by expressing high levels of sialoglycans, which bind to Siglec-9, a glyco-immune checkpoint molecule on NK cells. This binding inhibits NK cell cytotoxicity. Several viruses, such as hepatitis B virus (HBV) and HIV, also use a similar mechanism to evade NK surveillance. We found that NK cells from SARS-CoV-2-hospitalized patients are less able to function against cells expressing SARS-CoV-2 Spike protein than NK cells from SARS-CoV-2 mild patients or uninfected controls. We also found that the cytotoxicity of the Siglec-9 + NK subpopulation is indeed restrained by the inhibitory nature of the Siglec-9 molecule and that blocking Siglec-9 can enhance the ability of NK cells to target cells expressing SARS-CoV-2 antigens. Our results suggest that a targetable glyco-immune checkpoint mechanism, Siglec-9/sialoglycan interaction, may contribute to the ability of SARS-CoV-2 to evade NK immune surveillance.